2021
DOI: 10.2196/31129
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Acute Myocardial Infarction Using Asynchronous Electrocardiogram Signals—Preview of Implementing Artificial Intelligence With Multichannel Electrocardiographs Obtained From Smartwatches: Retrospective Study

Abstract: Background When using a smartwatch to obtain electrocardiogram (ECG) signals from multiple leads, the device has to be placed on different parts of the body sequentially. The ECG signals measured from different leads are asynchronous. Artificial intelligence (AI) models for asynchronous ECG signals have barely been explored. Objective We aimed to develop an AI model for detecting acute myocardial infarction using asynchronous ECGs and compare its perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In contrast, KM was more accurate for AF detection and can be attributed to differences in the artificial intelligence programs used by both devices. Each program has characteristics J o u r n a l P r e -p r o o f that allow its respective device to achieve a higher degree of accuracy in a particular heart rhythm, due to differences such as ECG datasets (15). Another possible explanation for the AW4's lower AF rhythm detection is that its artificial intelligence misinterpreted certain rhythm variations ( 16) such as, in the case of two patients, the Apple Watch recorded atrial fibrillation (AF) that was later confirmed to be premature atrial complexes (PACs).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, KM was more accurate for AF detection and can be attributed to differences in the artificial intelligence programs used by both devices. Each program has characteristics J o u r n a l P r e -p r o o f that allow its respective device to achieve a higher degree of accuracy in a particular heart rhythm, due to differences such as ECG datasets (15). Another possible explanation for the AW4's lower AF rhythm detection is that its artificial intelligence misinterpreted certain rhythm variations ( 16) such as, in the case of two patients, the Apple Watch recorded atrial fibrillation (AF) that was later confirmed to be premature atrial complexes (PACs).…”
Section: Discussionmentioning
confidence: 99%
“…The ECG is a ubiquitous and standardized tool in clinical medicine that reflects physiological and structural condition of the heart and also give valuable diagnostic clues for systemic conditions ( 19 ). Recent AI techniques have been applied to ECGs for the automatic classification or diagnosis of various cardiac diseases, such as arrhythmia and ischemia ( 28 31 ). Moreover, there is growing evidence that advanced AI techniques with deep convolutional neural networks are capable of detecting subtle signals and patterns from ECGs that do not fit traditional knowledge and are unrecognizable by the human eye ( 19 ); for example, an AI-enabled ECG algorithm has been shown to be capable of identifying patients with atrial fibrillation during normal sinus rhythm, which has important implications for atrial fibrillation screening and the management of patients with unexplained stroke ( 28 ); another AI-enabled ECG algorithm has been shown to be capable of predicting 1-year all-cause mortality even within a subset of patients with ECGs interpreted as normal by a physician ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of the use of artificial intelligence simulation, 3 asynchronous ECG leads (I, II, and V 5 ) were able to detect MI, and 4 leads (I, II, V 2 , and V 5 ) were an even better predictor. 30 Although no studies based on these conclusions have been performed in humans, these results provide a potential direction for an Apple Watch study. Developing an easier self-check protocol that requires only 3 or 4 recordings may help regular users avoid mistakes and save time.…”
Section: Study Protocol Limitationsmentioning
confidence: 90%